The Perception of Creaminess in Sour Cream. Issue 4 (10th June 2014) - Jervis, S.M.; Gerard, P.; Drake, S.; Lopetcharat, K.; Drake, M.A.
Abstract Creaminess is a consumer attribute that is frequently used to describe sour cream; however, creaminess is difficult to define or describe and is poorly understood because the mechanism or modality(s) for its perception remain uncertain. The objective of this study was to determine what sensory modality, or combination thereof, was responsible for the perception of creaminess in sour cream. Consumers (n = 274 baseline control, n = 100 each modality study) evaluated creaminess and overall liking of 12 samples representing the sensory space of commercial sour creams. Subsequently, in separate sessions, the effect of each sensory modality was evaluated: visual only, stirring, blindfolded stirring, blindfolded tasting, blindfolded tasting with nose clips and tasting with nose clips. An 11‐point creaminess rating scale was used to evaluate creaminess perception, and overall liking was evaluated using the 9‐point hedonic scale. The effect of session type (modality), panelist and fat content on creaminess and overall liking was evaluated using a mixed‐model analysis of variance. Flavor had the greatest impact on creaminess perception (P < 0.05) followed by visual assessment of sour cream while stirring. Creaminess perception of sour cream is assessed by an olfaction‐related mechanism and also by flow characteristics while stirring. Practical Applications In the wake of the health and wellness trend as well as the adult and childhood obesity epidemic, low‐fat and fat‐free dairy products are poised to fill a healthy diet niche. These products have historically performed poorly in comparison with their full‐fat counterparts. Creaminess is associated with dairy product liking. It is also an attribute that is difficult to measure due to the complexity of how it is perceived by consumers. This study established that flavor is the most important sensing modality when assessing the creaminess of sour cream orally, but that textural components also exist.